El Excentrico, 1968-07-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
July 5, 1968 [5 de Julio de 1968]. No volume or issue number. Cover has photo of a group of people in formal attire. The headline reads, "Club San Felipe's 10th Anniv. Ball. Saturday, July 20, 1968. Starlight Ballroom, $5.00 couple."